A Cross-Sectional Study of the Relationship Between BMI and Menstrual Cycle Regularity in Women of Reproductive Age in Pamekasan - Hermawati, Ratna; Praja, Dewangga Wahyu; Umam, Khoirul (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2025)
Obesity is increasingly recognized as a significant determinant of women’s reproductive health, particularly in relation to menstrual cycle irregularities. This cross-sectional study aimed to examine the relationship between Body Mass Index (BMI) and menstrual cycle regularity among women of reproductive age in Pamekasan, Indonesia. A total of 113 respondents aged 18–45 years were selected through simple random sampling. BMI data were obtained through anthropometric measurements, while menstrual cycle patterns were assessed using structured questionnaires. The study identified a notable trend: the likelihood of menstrual disturbances increased with higher BMI classifications. Women classified as overweight and obese experienced a higher prevalence of irregular menstrual cycles compared to those with normal BMI. These findings highlight the potential influence of excess body weight on hormonal regulation and ovulatory function. In rural settings like Pamekasan, where the prevalence of obesity is rising, this study emphasizes the need to integrate weight management into reproductive health programs. Targeted interventions through community education, nutritional counseling, and primary care integration could play a vital role in improving reproductive outcomes and reducing the burden of menstrual disorders.